Macrophages Polarized by Expression of ToxoGRA15II Inhibit Growth of Hepatic Carcinoma - Li, Yuanling; Poppoe, Faustina; Chen, Jian; Yu, Li; Deng, Fang; Luo, Qingli; Xu, Yuanhong; Cai, Yihong; Shen, Jilong (Frontiers in Immunology, 2017)
A growing body of evidence suggests that tumor associated macrophages (TAMs) are deeply involved in the hepatocellular carcinoma (HCC) proliferation, and account for the large proportion of infiltrated cells in tumor tissues and play a major role in promotion of tumor growth. On other hand, studies have demonstrated that Toxoplasma gondii virulence- associated molecule of dense granule protein (ToxoGRA15II) tends to induce classically activated macrophages (M1) differentiation. Thus we explored the M1 induced by ToxoGRA15II in vitro and its inhibitory impact on the proliferation, invasion, and metastasis of hepatic carcinoma in murine model. Here we constructed recombinant plasmid of pegfp-gra15II and subsequently ligate it to lentivirus (Lv) vector, with which RAW264.7 was transfected. The results showed that the transfected macrophages were polarized to M1. Co-culture of the M1 with Hepa1-6 cells showed a remarkable inhibition of migration and invasion of the tumor cells, and decreased expressions of MMP-9 and MMP-2 without notable apoptosis of Hepa1-6 cells. Subsequently, ToxoGRA15II-polarized macrophages inoculated to tumor bearing C57BL/6 mice were seen in both spleen and tumor tissues and tumor growth was sharply restricted. Particularly, IL-6 expression, which is closely associated with the cancer malignant behaviors, was significantly dampened in tumor tissues. In addition, expression of TNF-α and IL-12 mRNAs was increased whereas IL-6 and IL-10 mRNAs were downregulated in splenocytes. Our results indicate that the effector molecule of ToxoGRA15II may induce macrophage polarization to M1 that has a restrictive effect on tumor growth via its related cytokines profile in tumor and spleen tissues. Besides, ToxoGRA15 II, due to its early activation of specified cell population and nontoxicity to mammalians, has a potential value for a novel therapeutic strategy of enhancing host innate immunity against tumor development.